Coordinated Increased Expression of Cyclooxygenase2 and Nuclear Factor 𝜅B Is a Steady Feature of Urinary Bladder Carcinogenesis - Stylianos Kontos; Georgia Sotiropoulou-Bonikou; Athina Kominea; Maria Melachrinou; Eleni Balampani; Dionysis Bonikos (Advances in Urology)
Objectives. The inescapable relationship between chronic inflammation and carcinogenesis has long been established. Our objective was to investigate COX-2 and NF-𝜅B immunohistochemical expression in a large series of normal epithelium and bladder carcinomas. Methods. Immunohistochemical methodology was performed on formalin-fixed, paraffin-embedded sections from urinary bladder carcinomas of 140 patients (94 males and 46 females with bladder carcinomas). Results. COX-2 expression is increased in the cytoplasm of bladder cells, during loss of cell differentiation (𝑟s=0.61, 𝑃-value<.001) and in muscle invasive carcinomas (𝑃-value<.001). A strong positive association between tumor grade and nuclear expression of NF𝜅B has been established. A positive correlation between COX-2 and nuclear NF𝜅B immunoreactivity was observed. Conclusions. The possible coordinated upregulation of NF𝜅B and COX-2, during bladder carcinogenesis, indicates that agents inhibitors of these two molecules may represent a possible new treatment strategy, by virtue of their role in bladder carcinogenesis.